Assessment of Dofetilide or Sotalol Tolerability in the Elderly - Nikitha Yagnala PharmD; Lindsay Moreland-Head PharmD, BCCP; Joseph J Zieminski PharmD, BCCP; Kristin Mara MS; Shea Macielak PharmD, BCCP (SAGE Publishing, 2024)
Background: Dofetilide and sotalol are potassium channel antagonists that require inpatient QTc monitoring during initiation, due to increased risk of fatal arrhythmias. Elderly patients are especially subject to an increased risk of fatal arrhythmias due to polypharmacy, comorbidities, and physiologic cardiac changes with aging. This study will describe the tolerability and risk factors associated with the initiation of sotalol or dofetilide in patients ≥80 years of age. Methodology: This is a multicenter, retrospective, descriptive study of patients ≥80 years old who were initiated on either dofetilide or sotalol between May 8, 2018 and July 31, 2021 at institutions within the Mayo Clinic Health System. The percentage of patients who received nonpackage insert recommended doses was identified. Incidence of and reasons for dose reductions or discontinuations due to safety-related events or clinical concerns during the initial loading period were collected. Results: The final analysis included 104 patients. The majority of patients (75%) received nonstandard initial doses of dofetilide or sotalol based on baseline estimated creatinine clearance or QTc. Overall, 39% ( N  = 41) of patients experienced a dose reduction or discontinuation due to a safety-related event or concern. Patients who received nonstandard initial doses of dofetilide or sotalol had 4.7 times greater odds of experiencing a safety-related event requiring dose reduction or discontinuation. Conclusion: Following package insert dosing in elderly patients increases safety and tolerability relative to more aggressive dosing of dofetilide or sotalol.